Genres Hybridisation as an Author’s Strategy in “Night Film” Novel by M. Pessl - E. B. Kolomeytseva (Дискурс, 2025)
Introduction. Contemporary literature is built on the principles of playing, mixing high and low, and also mixing genres, therefore it requires research attention. The new meta modernist paradigm makes it possible to combine the tendencies of modernism and postmodernism, change genre strategies of authors. Studies of contemporary fiction allow supplementing the data of stylistics and genrology, since hybrids of genres, the so-called “zones of genre uncertainty”, are observed mostly there.Methodology and sources. In the article, as an example of a “genroid” – a work at the junction of genres – is considered a novel by M. Pessl “Night Film”, which is an example of the latest intellectual prose. The purpose of the article was to identify the author's strategy of hybridization of genres and means of implementation, the goals of this strategy, for which the method of linguistic analysis and comparative method were used. The sources of scientific data were articles from scientific journals, monographs and dissertations of Russian and foreign linguists and literary scholars.Results and discussion. The author of the novel achieves an effect of depth and cinematography of narration with the help of genre mixing strategy. It involves reader in interaction connection with the text and includes the text in a metamodernist concept of “new sincerity”. M. Pessl’s genre strategy includes the use of genre clichés of thriller, detective and horror novel (the effect of deceived expectations is triggered). The ironic mode of narration, change of narrative perspective, use of various stylistic means and visual prominence help to create cognitive empathy of the reader.Conclusion. The text exhibits the strategy of genre hybridization, multiple perspective of narration with the “text within the text” technique, the effect of an unreliable narrator, polycode text fragments, which creates a new metamodernist literature with its complex structure and textual cinematography. Thus, by mixing features of postmodernist and modernist literature, the metamodernist genre becomes a completely new phenomenon that requires further study.